2003
DOI: 10.1093/sleep/26.7.864
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind Clinical Trial Comparing Continuous Positive Airway Pressure with a Novel Bilevel Pressure System for Treatment of Obstructive Sleep Apnea Syndrome

Abstract: The NBL appeared to be as effective as CPAP for the treatment of OSAS but offered no advantages in patients receiving first-time therapy for OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
3
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 36 publications
2
62
3
4
Order By: Relevance
“…High adherence rates across the sample have been reported in other studies which have attempted to initiate a comparison of devices at the beginning of therapy. 9,16 Based on our experiences as well as previous report, 4 we had anticipated fairly poor adherence among patients who had a poor initial CPAP experience. The cumulative benefit of participating in the trial may have improved population adherence rates by providing intense support and maintenance of the therapy, along with proper mask adjustments and humidification.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…High adherence rates across the sample have been reported in other studies which have attempted to initiate a comparison of devices at the beginning of therapy. 9,16 Based on our experiences as well as previous report, 4 we had anticipated fairly poor adherence among patients who had a poor initial CPAP experience. The cumulative benefit of participating in the trial may have improved population adherence rates by providing intense support and maintenance of the therapy, along with proper mask adjustments and humidification.…”
Section: Discussionmentioning
confidence: 63%
“…4 Previous studies have attempted to either demonstrate improvement in adherence by early interventions or the use of variable pressure devices. Other studies attempting to utilize novel therapies at initiation of treatment have also failed to demonstrate clinically significant improvements in adherence rates compared to CPAP 9,17 ; despite some preference differences, most studies using bilevel devices also fail to demonstrate different clinically significant usage patterns. [5][6][7][8] Comparable to these studies, our study failed to demonstrate a significant improvement in adherence rates, regardless of improved daytime functioning and functional outcomes.…”
Section: Subjective Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In CPAP/BPAP adherence studies, [33][34][35] the machine mode has been thought to affect adherence. We found that the percentages of subjects using BPAP in the adherent and non-adherent groups were similar (15% and 16%, respectively), so we conclude that machine mode did not affect adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Bilevel positive airway pressure (PAP) devices allow for separate inspiratory and expiratory pressure settings that may be more comfortable for some patients. Although studies have not shown improvements in adherence, 44 select patients seem to tolerate bilevel PAP better than CPAP, particularly when high pressures are required or if patients had a prolonged period of poor initial tolerance to CPAP treatment. 45 In fact, AASM suggests bilevel PAP be used when CPAP pressure exceeds 15 cm H 2 O.…”
Section: Treatment Optionsmentioning
confidence: 91%